2016
DOI: 10.4314/ahs.v16i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IL-10 gene -819C/T polymorphism and the risk of inflammatory bowel disease: A meta-analysis

Abstract: Background: The -819C/T polymorphism in interleukin 10 (IL-10) gene has been reported to be associated with inflammatory bowel disease (IBD) ,but the previous results are conflicting. Materials and methods: The present study aimed at investigating the association between this polymorphism and risk of IBD using a meta-analysis.PubMed,Web of Science,EMBASE,google scholar and China National Knowledge Infrastructure (CNKI) databases were systematically searched to identify relevant publications from their inceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…For example, in a meta‐analysis based on 1890 IBD patients and 2929 controls, polymorphism of rs3021097 (C‐819 T) in IL‐10 was significantly associated with CD, but not statistically associated with IBD. 16 In a study of CD patients aged from 5 to 20 in Montreal, Canada, the genotype frequency of SNPs rs1800896, rs3021097, and rs1800872 in IL‐10 were not associated with CD, but the GCC haplotype was associated with the colonic location, and ACC haplotypes were associated with terminal ileum location in CD. 28 In addition to IL‐10 , SNPs rs3810936, rs6478108, and rs6478109 of TNFSF15 gene were extremely significantly correlated with CD in Korean children, and their OR values were all over 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a meta‐analysis based on 1890 IBD patients and 2929 controls, polymorphism of rs3021097 (C‐819 T) in IL‐10 was significantly associated with CD, but not statistically associated with IBD. 16 In a study of CD patients aged from 5 to 20 in Montreal, Canada, the genotype frequency of SNPs rs1800896, rs3021097, and rs1800872 in IL‐10 were not associated with CD, but the GCC haplotype was associated with the colonic location, and ACC haplotypes were associated with terminal ileum location in CD. 28 In addition to IL‐10 , SNPs rs3810936, rs6478108, and rs6478109 of TNFSF15 gene were extremely significantly correlated with CD in Korean children, and their OR values were all over 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, for CD, genetic risk prediction is still in the exploratory stage, and no highly correlated loci have been identified so far, which is of low clinical efficacy. For example, in a meta‐analysis based on 1890 IBD patients and 2929 controls, polymorphism of rs3021097 (C‐819 T) in IL‐10 was significantly associated with CD, but not statistically associated with IBD 16 . In a study of CD patients aged from 5 to 20 in Montreal, Canada, the genotype frequency of SNPs rs1800896, rs3021097, and rs1800872 in IL‐10 were not associated with CD, but the GCC haplotype was associated with the colonic location, and ACC haplotypes were associated with terminal ileum location in CD 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literatures which studied the connection of IL-10 polymorphisms with disease susceptibility were extensively reported. IL-10 polymorphisms were considered to be connected with multiple disease susceptibility such as ischemic stroke, pulmonary tuberculosis, HIV-1, nasopharyngeal carcinoma and multiple sclerosis, gastric cancer and inflammatory bowel disease [17][18][19][20][21][22][23]. The increased risk or reduced risk can be detected due to diverse reasons including studied races, sample size, genotyping methods and source of control population, which may lead to different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that elevated level of IL-10 activates the transcription factor Fox P3 which may subsequently lead to the production T regulatory cells. Polymorphism in the promoter regions of IL-10 gene À1082(G/A), À819(C/T), and À 592 (C/A) is well established and showed significant association with various infectious diseases, autoimmunity, cancer D, and diabetic retinopathy [35][36][37]. These IL-10 promoters, À1082(G/ A), À819(C/T), and À 592(C/A) polymorphisms, are associated with resistance to sepsis in the Caucasian population [38,39].…”
Section: Role Of Cytokine Gene Polymorphism In Sepsismentioning
confidence: 99%